The Value of Research Methods and Approaches in Modern Public Administration Research - Sifiso Mofokeng (International Journal of Law, Social Science, and Humanities, 2026)
The 21st century has immensely shaped the face and art of governance with the rise of globalisation, technological innovations and rising public expectations. With this in mind, research methods, designs, and approaches have emerged as foundational pillars for advancing modern public Administration for practice and scientific research. Modern Public Administration faces countless challenges and problems ranging from policy misalignments, service delivery failures, lack of citizen participation and engagement, and many other issues requiring systematic and analytical approaches. Thus, these research methods, designs, and approaches serve as a backbone for understanding and resolving societal problems in a manner that allows public administrators to make evidence-based decisions. This study employed a qualitative approach relying on secondary data and thematic content analysis of relevant scholarly literature and documents. This analysis revealed that well-applied research methods and designs enable public administrators to trace and resolve public policy and other public administration problems. The study found that research methods extend beyond academic research and that these methods are practical solutions for the existing governance challenges. The study concluded that Afrocentric approaches and methods are central to resolving African governance problems and Public Administration shortfalls.